IMPLEMENTASI TEORI BELAJAR BEHAVIORISTIK DALAM PEMBELAJARAN PAI DI SMPN 06 SUNGAI ROTAN KABUPATEN MUARA ENIM - Tri Alawiyah; Fajri Ismail; Muhammad Win Afgani (ADIBA : JOURNAL OF EDUCATION, 2023)
The purpose of this study is to understand the importance of applying behavioristic theories to the learning of Islamic Religious Education. The method used by the author is descriptive qualitative which seeks to explain the application of behavioristic theory so that it is able to produce behavior change towards students. Through this study, the author tries to uncover the methods used by PAI teachers at Nogopuro Elementary School in Yogyakarta as well as changes in student behavior using a behavioristic theory approach. Based on the results of the study it was found that the application of Behavioristic learning theory to PAI learning used reinforcement, motivation, stimulus, and practice. While changes in student behavior towards posistif are motivated in learning, interactive, strengthening memory, and tolerance.